STRATEGIES FOR REDUCING YOUTH UNEMPLOYMENT IN SOUTH AFRICA (Proceedings of the World Conference on Children and Youth, 2021)
Youth unemployment is one of the major challenges that the majority of countries worldwide are faced with currently. In South Africa, youth unemployment has been escalating, despite the introduction of initiatives by the government to reduce unemployment. This study aims to identify the root causes of youth unemployment in South Africa and suggesting solutions to reduce youth unemployment. The researcher utilized secondary data obtained from the Quarterly Labour Force Survey by Statistics South Africa, time series data from the South African Reserve Bank and the Department of Higher Education and Training websites for conducting data analysis. The type of research methodology utilized by the research is a Quantitive research method. The findings of the study indicate that the root causes of youth unemployment include the poor education system resulting in skills mismatch in the economy. An econometric regression model was conducted by the researcher in Eviews 8 statistical data analysis software using time series data from the South African Reserve Bank, with youth unemployment being the dependent variable. The results of the econometric regression model indicated that the variables inflation rate, Gross value added a proxy for Gross Domestic Product and the Total loan debt of the nation were statistically significant at a 5% level of significance. This means that youth unemployment is influenced by the inflation rate, Gross Domestic Product and the Total loan debt of the nation or government debt. Lastly, the study discusses the recommendations to policymakers on how to reduce youth unemployment in South Africa. The results of the econometric regression indicate that youth unemployment is influenced by macroeconomic factor namely the rise in the inflation rate, decline in Gross domestic product, an increase in the government debt which deprives youth in terms government investing in youth empowerment programmes. The researcher concludes by giving policy recommendations on possible programmes that can be implemented to reduce youth unemployment.
Keywords: Youth unemployment; skills-mismatch; causes; solutions